2009
DOI: 10.3319/tao.2008.04.08.01(t)
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Survey of Taiwan and Its Preliminary Interpretations

Abstract: AB STRACTTo achieve an im proved over all un der stand ing of the tec ton ics of Tai wan, an is land-wide mag netic sur vey, es pe cially in the mostly in ac ces si ble moun tain ranges, was car ried out from July 2003 to Feb ru ary 2004. In to tal, 6063 mag netic points were sur veyed at an av er age spac ing of 2 km. Af ter data re duc tions, a new mag netic anom aly map of Tai wan was con structed. The map shows the range of mag netic anom a lies mostly dis trib ut ing be tween -400 to 400 nT. Anom a lies i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…The variations in the geomagnetic field caused by solar activity are most likely the same within a small region generally considered to be global effects (Chapman and Bartels 1940). Other sources such as induced geomagnetic fields caused by differences in electrical structure (Lilley and Arora 1982;Lilley 1984;Horng et al 1992;Hsu et al 1998;Lilley et al 1999;Yen et al 2009), pre-earthquake magnetic anomalies resulting from stressed rocks (Yanagihara and Nagano 1976;Rikitake 1979;Shiraki 1980;Chen and Fung 1985;Gong 1985;Chen et al 2006), and the magnetic coast effect due to the distinct conductivity between continental rocks and sea water (Parkinson 1959(Parkinson , 1962(Parkinson , 1983Bennett and Lilley 1971;Lilley and Bennett 1972;Parkinson and Jones 1979;Delaurier et al 1983;Yukutake et al 1983;Ogawa et al 1986;EMSLAB Group 1988;White et al 1990;Kellett et al 1991;Hitchman et al 2000;Armadillo et al 2001;Lee et al 2007;Bertrand et al 2009Bertrand et al , 2012Chiang et al 2010) affect the geomagnetic field within a local area. The GZH, HC, and PHU stations have similar geomagnetic latitudes from 10.92 -13.27°N.…”
Section: Discussionmentioning
confidence: 99%
“…The variations in the geomagnetic field caused by solar activity are most likely the same within a small region generally considered to be global effects (Chapman and Bartels 1940). Other sources such as induced geomagnetic fields caused by differences in electrical structure (Lilley and Arora 1982;Lilley 1984;Horng et al 1992;Hsu et al 1998;Lilley et al 1999;Yen et al 2009), pre-earthquake magnetic anomalies resulting from stressed rocks (Yanagihara and Nagano 1976;Rikitake 1979;Shiraki 1980;Chen and Fung 1985;Gong 1985;Chen et al 2006), and the magnetic coast effect due to the distinct conductivity between continental rocks and sea water (Parkinson 1959(Parkinson , 1962(Parkinson , 1983Bennett and Lilley 1971;Lilley and Bennett 1972;Parkinson and Jones 1979;Delaurier et al 1983;Yukutake et al 1983;Ogawa et al 1986;EMSLAB Group 1988;White et al 1990;Kellett et al 1991;Hitchman et al 2000;Armadillo et al 2001;Lee et al 2007;Bertrand et al 2009Bertrand et al , 2012Chiang et al 2010) affect the geomagnetic field within a local area. The GZH, HC, and PHU stations have similar geomagnetic latitudes from 10.92 -13.27°N.…”
Section: Discussionmentioning
confidence: 99%
“…The background map of the geomagnetic anomaly in Fig. 1 is adapted from Yen et al (2009), which provides the information about underground magnetic structures. After the earthquake occurs, the seismic waves propagate through whole island-wide and triggered co-seismic fluctuations have been recorded by the sensors/instruments.…”
Section: Experiments Setup and Observationmentioning
confidence: 99%
“…Geomagnetic anomaly map and the locations of the Hualien Earthquake and measurement stations. The geomagnetic anomaly using the same data with Yen et al (2009) and doing low-pass filtering process after a careful data selection to eliminate spikes. The red star is the 2018 M 6.2 Hualien Earthquake; the solid circle denoted the QuakeFinder systems; the solid diamonds mark the co-location seismometers; the solid triangles shows the tiltmeters and micro-barometers; the open triangles are infrasound systems; the solid rectangles are fluxgate magnetometers.…”
Section: Experiments Setup and Observationmentioning
confidence: 99%
“…Chen et al (2009a) prudently examined data quality of the 11 stations by the Chapman-Miller method (Chapman and Miller, 1940), and found that tiny signals caused by the magnetic lunar effects can be observed. Although these total intensity data retrieved from this network are difficult to be used to observe changes in direction of magnetic fields, good quality and a long observation period (from 1988 to now) of data are sufficient to be utilized in most geomagnetic studies (Chen et al, , 2009a(Chen et al, , 2010(Chen et al, , 2011aLiu et al, 2006;Yen et al, 2004Yen et al, , 2009). The M = 9.0 Tohoku earthquake (142.38 • E, 38.30 • N) occurred on 11 March 2011, striking northern and eastern Japan as the most destructive earthquake thus far in the 21st century.…”
Section: Introductionmentioning
confidence: 99%